Teaching Vocabulary to Grade XI Students through Duolingo Application at Senior High School - Amelia, Riski; Jamiluddin, Jamiluddin; Eisenring, Moh. Abraham Akbar; Said, Mawardin M. (Lectura : Jurnal Pendidikan, 2025)
This study focuses on the effectiveness of using the Duolingo application in teaching vocabulary to grade XI. This study used a quasi-experimental design with two classes: experimental and control. The experimental class received treatment using Duolingo media, while the control class was taught using conventional media. Pre-tests and post-tests were used to assess improvements in students’ vocabulary. The results of the study indicate that the use of the Duolingo application is effective and can improve students’ vocabulary, as evidenced by the average score of the experimental class increasing from 78.10 to 95.5. The Mann-Whitney test showed a significant difference between the two classes (p<0.05), indicating that the use of the Duolingo application is effective in teaching vocabulary. In addition, the findings reveal that students in the experimental class demonstrated higher levels of engagement, motivation, and confidence when learning new vocabulary through the application. The interactive features of Duolingo, such as gamification and immediate feedback, contributed to a more meaningful learning experience. These advantages suggest that mobile-based language learning tools like Duolingo can play a significant role in enhancing language acquisition in formal educational settings. Therefore, it is recommended that teachers consider integrating technology-enhanced instructional media to complement traditional teaching methods in order to maximize students’ outcomes in vocabulary mastery.